Analisis Kebutuhan Pengembangan E-Modul Interaktif Ekonomi Digital Untuk Meningkatkan Literasi Ekonomi Mahasiswa - Desi Budiono; Intan Utami (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The advancement of digital technology necessitates a transformation in learning approaches, including in Digital Economics courses. However, the available instructional media have not fully addressed students' needs in understanding technology-based economic concepts. This study aims to analyze the need for developing interactive e-module–based learning media in digital economics to enhance students’ economic literacy. This research employs a descriptive quantitative approach, involving 20 students from the Economic Education Program at Universitas Muhammadiyah Metro who had previously completed the Digital Economics course. The data were collected using a student questionnaire focused on their expectations regarding e-module features, covering eight key indicators. The results show that most students expect learning media to be interactive, user-friendly, visually appealing, and integrated with real-world digital economic practices. These findings highlight the urgency of developing adaptive interactive e-modules that align with the characteristics of the digital generation and support active learning processes. The study concludes that students have high expectations for the presence of digital economics learning media capable of enhancing economic literacy and overall learning engagement.